2021
DOI: 10.3390/jcm10163703
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Outcomes after Surgical versus Transcatheter Aortic Valve Replacement with Newer Generation Devices

Abstract: The superiority of transcatheter (TAVR) over surgical aortic valve replacement (SAVR) for severe aortic stenosis (AS) has not been fully demonstrated in a real-world setting. This prospective study included 5706 AS patients who underwent SAVR from 2010 to 2012 and 2989 AS patients who underwent TAVR from 2017 to 2018 from the prospective multicenter observational studies OBSERVANT I and II. Early adverse events as well as all-cause mortality, major adverse cardiac and cerebrovascular events (MACCEs), and hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…The high PPM implantation rate observed in our study may be partially explained by a low threshold for pacemaker implantation at our hospital. In the literature, a PPM rate of 15.5% and 16.2% is reported after TAVI, which is still higher than in our TEAVR patients [20,21]. In this trial, the PPM rate of TAVI patients was also 12.5%.…”
Section: Clinical Follow-upcontrasting
confidence: 55%
See 1 more Smart Citation
“…The high PPM implantation rate observed in our study may be partially explained by a low threshold for pacemaker implantation at our hospital. In the literature, a PPM rate of 15.5% and 16.2% is reported after TAVI, which is still higher than in our TEAVR patients [20,21]. In this trial, the PPM rate of TAVI patients was also 12.5%.…”
Section: Clinical Follow-upcontrasting
confidence: 55%
“…This explanation also applies to the TAVI subgroup of this study ( n = 8), in which no MACCE was seen also. Other studies reported a MACCE rate of 12% and 18.2% after TAVI and a MACCE rate of 15.8% and 17.6% after conventional open AVR [ 20 , 21 ]. In this trial, 7.0% of TEAVR patients experienced a MACCE.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-eight centers met the data quality criteria required by the study protocol and their data are included in this analysis. 7 The Ethical Committee of each participating center granted permission to participate in the OBSERVANT II study. All patients included in this study gave informed consent to the scientific treatment of their data on an anonymous form.…”
Section: Methodsmentioning
confidence: 99%
“…Data for the present analysis were obtained from the OBSERVANT II study, a national, observational, prospective, multicenter cohort study that enrolled consecutive AS patients who underwent TAVR at 30 Italian centers between December 2016 and September 2018. Twenty‐eight centers met the data quality criteria required by the study protocol and their data were included in this analysis 8 . Participating centers are listed in the Supporting Information: .…”
Section: Methodsmentioning
confidence: 99%
“…Twentyeight centers met the data quality criteria required by the study protocol and their data were included in this analysis. 8 Participating centers are listed in the Supporting Information: Material. The Ethical Committee of each participating center granted permission to participate in the OBSERVANT II study.…”
Section: Data Sourcementioning
confidence: 99%